2022
DOI: 10.3389/fcvm.2022.913437
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Uric Acid Levels and Traditional Cardiovascular Risk Factors in Xiamen Residents of China: A Real-World Study

Abstract: BackgroundSerum uric acid (SUA) levels was associated with cardiovascular diseases and cardiovascular events. However, the relationship between SUA levels and traditional cardiovascular risk factors has not been well-established among Xiamen residents. Our study aimed to estimate the relationship between SUA levels and cardiovascular risk factors among Xiamen residents using real-world data.MethodsParticipants were enrolled from eight community health service centers in Xiamen, China. Participants were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Serum uric acid levels were strongly associated with cardiovascular events in patients at high risk of heart disease and in women (Feig et al, 2008). A study including the elderly showed that high uric acid levels were associated with all‐cause and cardiovascular mortality (Wu et al, 2015; Zhang et al, 2022). However, previous studies were mainly retrospective or cross‐sectional studies, and the analysis mainly focused on the correlation between OSA and uric acid level, the prognosis of OSA and ACS, and the relationship and risk between uric acid and coronary heart disease, and failed to confirm the effect of OSA on prognosis in patients with ACS complicated with hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…Serum uric acid levels were strongly associated with cardiovascular events in patients at high risk of heart disease and in women (Feig et al, 2008). A study including the elderly showed that high uric acid levels were associated with all‐cause and cardiovascular mortality (Wu et al, 2015; Zhang et al, 2022). However, previous studies were mainly retrospective or cross‐sectional studies, and the analysis mainly focused on the correlation between OSA and uric acid level, the prognosis of OSA and ACS, and the relationship and risk between uric acid and coronary heart disease, and failed to confirm the effect of OSA on prognosis in patients with ACS complicated with hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…CAD has a variety of risk factors, and often reflected in clinical manifestations such as frequent episodes of angina pectoris, intractable heart failure, and malignant arrhythmias [ 35 ]. Elevated uric acid levels are associated with traditional CAD risk factors, including hypertension, diabetes mellitus, dyslipidemia, and obesity [ [9] , [10] , [11] ]. Previous prospective studies have shown a concomitant increase in the risk of developing hypertension with increased circulating uric acid concentrations [ 43 ].…”
Section: The Correlation Between Hyperuricemia and Cadmentioning
confidence: 99%
“…Although some studies question the independent risk role of uric acid and more studies suggest that hyperuricemia has a negative impact on the onset, progression and prognosis of CAD [ [5] , [6] , [7] , [8] ]. There is also evidence that hyperuricemia is inextricably linked to traditional risk factors for CAD, which may have jointly contributed to the onset and development of CAD [ [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%